Curvature and Feature-Aware Print-Paths from Hexahedral Meshes for Additive Manufacturing. (December 2021) - Gunpinar, Erkan
Abstract: Recently proposed meshing techniques allow the generation of high-quality hexahedral meshes (hex-mesh) whose edges follow the surface feature and curvature-lines. This study investigates their use in additive manufacturing for the generation of curvature and feature-aware print-paths (tool-paths). A hex-mesh consists of 8-noded hexahedra (hex-cells) and a cuboid-like sub-volume is structured (i.e., valence for the inner edges is only four), which is represented using a three-dimensional (3D) array of hex-cells. All cuboid-like sub-volumes (called C-partitions ) are first enumerated by growing them from singular-edges (i.e., a series of connected same-valence singular-edges that are not two on the boundary or four in the interior). These C-partitions are then selected one-by-one according to a cost function based on several criteria including alignment of print-paths along the feature curves and curvature directions. Remaining C-partitions are split if they intersect the (previously) selected C-partitions. The C-partitions are iteratively chosen and split until all hex-mesh is covered by the (selected) C-partitions. Print-paths are arranged along (predetermined) direction(s) in a C-partition, and tubes representing deposited material (in AM) around the print-path overlap at some locations. Thus, these tubes are repaired via tube adjustment operators, in which their location and material deposition radii at those locations are modified. As a proof of concept, curvature and feature-aware print-paths are finally validated using an AM simulator and machine. Highlights: Feature and curvature-aware print-paths are generated for additive manufacturing. Hexahedral meshes are used as input. Cuboid-like volumes are obtained from a hexahedral mesh. Each volume are separately filled with print-paths.